Local knowledge about medicinal plants does not influence the self-reported well-being of inhabitants of the semi-arid region of northeastern Brazil - Sousa, Bruno Melo; Albuquerque, Ulysses Paulino; Araújo, Elcida Lima (Ethnobotany Research and Applications, 2022)
Background: The literature gathers several pieces of evidence on the use of medicinal plants for disease treatment, showing that local knowledge about medicinal plants is a relevant reservoir of information for local health treatment. However, a direct positive correlation between this local knowledge and the perception of well-being is still unknown, as well as the potential impacts of this correlation on humans’ quality of life. In this study, we hypothesized that the local knowledge of medicinal plants positively impacts well-being. Methods: The study was conducted in six communities inside the Catimbau National Park, Northeastern Brazil, dependent on using plants to treat diseases. Local knowledge about medicinal plants and self-reporting well-being were collected by free listing and semi-structured interviews, respectively. The well-being index of each participant was calculated by summing the scores of their answers for seven questions that covered individual aspects and food and financial security. A generalized linear model was conducted to assess the relationship between the knowledge of ethnospecies and the well-being index of participants. Results: Participants cited an average of 10.06 ethnospecies and 8.18 therapeutic targets. The mean score of the well-being index was 22.22. We found no association between the local knowledge of medicinal plants and the well-being index. Conclusion: The local knowledge of medicinal plants is not a determining factor of local human well-being. Keywords: happiness, ecosystem services, ethnobotany.